Selected dietary (poly)phenols inhibit periodontal pathogen growth and biofilm formation. Issue 3 (13th January 2015) - Shahzad, Muhammad; Millhouse, Emma; Culshaw, Shauna; Edwards, Christine A.; Ramage, Gordon; Combet, Emilie
Abstract : Periodontitis (PD) is a chronic infectious disease mediated by bacteria in the oral cavity. Abstract : Periodontitis (PD) is a chronic infectious disease mediated by bacteria in the oral cavity. (Poly)phenols (PPs), ubiquitous in plant foods, possess antimicrobial activities and may be useful in the prevention and management of periodontitis. The objective of this study was to test the antibacterial effects of selected PPs on periodontal pathogens, on both planktonic and biofilm modes of growth. Selected PPs ( n = 48) were screened against Streptococcus mitis (S. mitis), Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans), Fusobacterium nucleatum (F. nucleatum) and Porphyromonas gingivalis (P. gingivalis) . The antibacterial potential of each compound was evaluated in terms of planktonic minimum inhibitory concentration (PMIC) and planktonic minimum bactericidal concentration (PMBC) using standardized broth microdilution assays. The most active PPs were further tested for their effect on mono-species and multi-species biofilms using a colorimetric resazurin-based viability assay and scanning electron microscopy. Of the 48 PPs tested, 43 showed effective inhibition of planktonic growth of one or more test strains, of which curcumin was the most potent (PMIC range = 7.8–62.5 μg mL −1 ), followed by pyrogallol (PMIC range = 2.4–2500 μg mL −1 ), pyrocatechol (MIC range = 4.9–312.5 μg mL −1 ) and quercetin (PMIC range = 31.2–500 μg mL −1 ). At this concentration, adhesion of curcumin and quercetin to the substrate also inhibited adhesion of S. mitis, and biofilm formation and maturation. While both curcumin and quercetin were able to alter architecture of mature multi-species biofilms, only curcumin-treated biofilms displayed a significantly reduced metabolic activity. Overall, PPs possess antibacterial activities against periodontopathic bacteria in both planktonic and biofilm modes of growth. Further cellular and in vivo studies are necessary to confirm their beneficial activities and potential use in the prevention and or treatment of periodontal diseases.